Examination into nanomaterials, nanofibers and nanoparticles advances for wound healing and scaffolds in tissue engineering application: A review - Jesubori W. Sojobi; Oluwatoyin L. Bankole; Daniella C. Ulelu; Ojo S.I. Fayomi (Results in Surfaces and Interfaces)
There is an urgent need for effective wound coverings that promote healing and lower the risk of infection, as there are approximately 165 million wound cases worldwide each year. However, there is little information on nanomaterials that are affordable in underdeveloped countries that are relevant for wound healing and tissue regenerative applications. This work reviews the use of polymers and bioactive polymers e.g., polyethylene, polypropylene, epoxy, and poly(methyl methacrylate) (PMMA), Polyvinyl alcohol (PVA), chitosan, honey, hydrogel etc., as nanocomposites for wound healing and scaffolds for tissue engineering applications. The nanomaterial properties can be tuned as desired via precisely controlling the size, shape, synthesis conditions, and appropriate functionalization. The biocompatibility and antibacterial properties of the nanocomposite are improved bioactive ingredients. In particular, we describe and define various terms relating to nanoparticles, nanocomposites and nanofibers. Various nanomaterial synthesis methods, including top-down and bottom-up approaches, are discussed. Various synthesized nanofiber composites for various applications from other research works are also reviewed. Finally, we conclude by discussing the most relevant tests to be carried out for wound healing and affordable scaffolds for tissue engineering applications in underdeveloped and developing countries.